PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) UNTUK SISWA KELAS V SEKOLAH DASAR - Aulia, Imam; Hakim, Mansur; Handika, Ilham; Affandi, Hamdian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop valid and practical student worksheets (LKPD) based on problem based learning (PBL) for elementary school students. This type of research is research and development using the 4D model (define, design, develop, and disseminate). The data collection technique used is a questionnaire. The data analysis technique is validity and practicality analysis. Product validity is assessed by two validators with a Likert scale analysis. Practicality is determined from the results of the student response questionnaire. The results of the data analysis show that the developed LKPD: (1) Valid, with an average value of 93.3%, (2) Practical, with an average percentage of student responses of 85.88%. So it can be concluded that the development of student worksheets (LKPD) based on problem based learning (PBL) for elementary school students is valid and practical, and effective in improving student abilities.